(untitled) (Palíndromo, 2020)
In this article, an application of the theories of possible worlds in the study of the image and its effects is proposed. After a brief introduction to this theoretical universe, we move on to the context of visual arts, in which there are not many published works on the subject. A notion of “ways of worldmaking” is developed, which emerges from an active image-fiction, established by the “fingere” of the artist. The attitude of self-denunciation of this image allows the viewer to find evidence of its manipulated quality, which ultimately allows for a cognitive change in relation to the constructions and changes that we can make in our so-called real world. After a case study, it is concluded that, like the image, reality is a manipulable matter, and the understanding of this opens up paths for the construction of new contexts in the present.